Teaching Speaking through Blind Man’s Buff Game to the Students at Secondary School Level - Maria Ramasari (STKIP PGRI Lubuklinggau, 2018)
The aim of this research was to find out whether or not it was significantly effective to teach speaking through Blind Man’s Buff game to the students at Secondary School Level. The researcher used pre-experimental method in conducting this research. The population of this research was all the eighth grade students of SMP Muhammadiyah 1 Lubuklinggau. The sample was taken through cluster random sampling; it was class VIII B that consisted of 31 students. The data were collected by using oral test, and the data obtained from the research were analyzed by using four techniques: 1) Students’ Individual Score, 2) Conversion of Score Range, 3) Normality Testing, and 4) The Paired t-test. The result of this research were (1) the average score in the pre-test was 47.48, (2) the average score of post-test was 68.71, and (3) the result of matched t-test was 9.92, which was higher than 1.697 critical value of the table of df 30 (31-1) with 95% significant level tailed t-test. In conclusion, the null hypothesis was rejected and the alternative hypothesis was accepted. It meant that it was significantly effective to teach speaking through Blind Man’s Buff game to the students at Secondary School Level.